Black Ice - Fitzpatrick, Becca (New York : Simon & Schuster BFYR, 2014)
Britt goes hiking in the Grand Tetons of Wyoming with her ex-boyfriend Calvin, but trouble arises when she is caught in a blizzard, taken hostage by fugitives, finds evidence of murders, and learns whom to trust and whom to love.
Keywords: Survival -- Juvenile fiction; Hostages -- Juvenile fiction; Love stories; Survival -- Fiction; Hostages -- Fiction; Love -- Fiction; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Social Issues / New Experience; JUVENILE FICTION / Social Issues / Emotions & Feelings